THE IMPLEMENTATION OF PORTFOLIO METHODIN TEACHING WRITING:A Case Study on the first Grade Students of SMA Pasundan 1 Cimahi - Erdita Prasanti Riantini, - (2011)
The research investigated the implementation of portfolio method in teaching writing on the first grade students of SMA Pasundan 1 Cimahi. It was also aimed to find out the problems faced by the students in making portfolio. The strategies that the students use in handling the problems in making portfolio were also investigated in order portfolio method can be conducted effectively in the future.The research employed case study design in which the data were collected through observations and interviews. The subjects were first grade students of SMA Pasundan 1 Cimahi. Six students were involved as the respondents in this research. The result of the research revealed the phases of portfolio method, which were explanation by the teacher, class discussion, pre-writing, drafting, peer reviewing, revising, teacher reviewing, editing and submitting the final draft. The problems faced by the students were laziness, time management, the lack of ideas, poor grammatical mastery and lack of vocabulary, unclear explanation and instruction, insufficient feedback from teacher, problem in doing peer reviewing, lack of facilities, and problem in keeping a record. The strategies to handle the problems were different and depend on the students themselves. Changing students' fallacy toward portfolio, working together with friends, clear explanation and guidance from teacher, renting computer, and keeping students' drafts in the special boxes were the strategies to handle the problems in making portfolio. For teachers who interested in implementing portfolio, it is suggested to make a careful planning. The teacher also suggested to clearly introduce the concepts and provide detailed guidelines to help students develop their portfolio. For further research, the researcher suggests that the implementation of portfolio method in other level is necessary to be analyzed.